2017
DOI: 10.1177/0969733017722824
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress in Iranian pediatric nurses

Abstract: Since many pediatric nurses clearly face moral distress while taking care of children, it is necessary to consider measures for preventing or decreasing situations that would lead to this distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 29 publications
0
49
1
1
Order By: Relevance
“…In studies of non-ICU nurses, root causes generally centered on team and system problems such as witnessing medical students perform treatments only to improve their skills, being unqualified to care for patients, feeling pressure to alter practice in order to reduce costs, and encountering conflict with administration. 27,33 However, in their study of non-ICU nurses, Wenwen et al 31 found that the most problematic causes of moral distress were initiating and continuing life-sustaining treatment when it is believed that these are pointless.…”
Section: Experiences Of Moral Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of non-ICU nurses, root causes generally centered on team and system problems such as witnessing medical students perform treatments only to improve their skills, being unqualified to care for patients, feeling pressure to alter practice in order to reduce costs, and encountering conflict with administration. 27,33 However, in their study of non-ICU nurses, Wenwen et al 31 found that the most problematic causes of moral distress were initiating and continuing life-sustaining treatment when it is believed that these are pointless.…”
Section: Experiences Of Moral Distressmentioning
confidence: 99%
“…Participants in the studies varied, including intensive care unit (ICU) nurses, 8,28,32,34,37,38,40 mixed wards, 27,[29][30][31]36,41 HIV nurses, 35 oncology nurses, 39 and pediatric nurses. 33…”
mentioning
confidence: 99%
“…In the pediatrics department, studies have shown that due to limited professional authority on the part of nurses, moral distress leads to impairment in safe patient care. The most important contributor to moral distress in the pediatric ward is to observe medical students performing painful procedures on children to acquire skills (18,22). Table 1 presents an overview of the included articles.…”
Section: Organizational Barriersmentioning
confidence: 99%
“…Several studies have shown that nursing staff shortages in Iran are caused by multiple factors. In particular, low wages and poor working environments characterized by moral distress have been implicated as causal factors of nursing shortages in Iran (Azimian, Negarandeh, & Fakhr‐Movahedi, ; Dehaghani, Akhormeh, & Mehrabi, ; Ghasemi, Negarandeh, & Janani, ; Mosadeghrad, ; Tabatabaee, Nekoie‐Moghadam, Vafaee‐Najar, & Amiresmaili, ; Valizadeh et al., ; Zarea, Negarandeh, Dehghan‐Nayeri, & Rezaei‐Adaryani, ).…”
Section: Introductionmentioning
confidence: 99%